MULTILINGUALISME DAN GENDER DALAM LANSKAP LINGUISTIK USAHA PANGKAS RAMBUT DI KECAMATAN JOMBANG - Ayu Fitriawati; Frans Asisi Datang (Sunan Kalijaga State Islamic University Yogyakarta, 2024)
In multilingual societies of former Western colonies, modernism is often pinned on English as the international lingua franca, thus shifting the mother tongue/regional language which is considered of lower value. In the discussion of post-structuralism, language use contributes to identity construction, one of which is gender identity. Inequality of gendered cultural expectations in multilingualism is problematic as it reasons gender disparities in the workforce, among many others. Using a mixed method of quantitative and qualitative study, this research investigates patterns of language dominance on public signs belonging to space with the concept of gender segregation, specifically salons/barber shops, in the urban area of Jombang Regency, that is Jombang sub-district, through a Linguistic Landscape (LL) study. In result, all signs with the target market of women, men, and both display the call for modernism through constant use of English and Indonesian language, which notably overrides Javanese as the mother tongue and everyday language of the people. However, multilingualism in women exhibits the “new economic pattern” where education and work opportunities are equal/almost equal. Even so, there appears to be an indication of higher expectations for men to be capable of understanding English than women through significant use of monolingual English signs.